(Love and Love) in the light of the significance of Quranic (Journal of the College of Education for Women, 2019)
Thanks allah and peace be upon our prophet muhammed and upon his family and hisfollowers……Love means in holy quran what comes to people s mind nowadays and what it inspired itssigni ficence is related with sensual desire and it means adore and passion .by the waytheword (ishiq) adore wasn’t mentioned in holy quran which means that both of their bases arefarfrom each oiter in m eaning.The significance of love means virtue while adore means the excess and desire so adore isdis praised . as al askari said (died 395h )between love and adore.adore is the strain of desireto get the purpose from lovers if it was ahuman who intended to make love affairs.Today both of love and adore changed in their meaning as their sighificancaes are aboutfrom each other in the contemporary expression so they use the word love for adore lovesyhonyms.As a quran expression is not like that whevev man is advanced loves with his mind butwhenever man is being low he loves with his senses .as quran expressions both of theirsignificances are related with the universe strncture goodneaa ,gift, worshiping and lovegoodness. So all hearts love and satisfied with al might god worshiping allah stand on threebases:love,fair,hope.Which differs from loving desire and preferring it and keeping on to get it in the sufiphilosophy the word is called for the god fear ingness loving god and religious mau.